Correlation of Hardware Demonstrations and Student Understanding - Squire , James C.; Sullivan , Gerald A.; Brooke , George M. (Theory and Applications of Engineering Research Vol. 1, 2023)
This chapter aim to investigate the pedagogic effect of demonstration construction quality. The hypothesis that the construction finish of a classroom demonstration affects its pedagogic value will be assessed by constructing two different demonstrations: a remote controlled vehicle and a laser-based audio communication device. This study looks at two types of construction: "raw" and "polished." Raw demonstrations use prototype-quality construction techniques that include exposed solderless breadboards, whereas polished demos use production-quality construction techniques aimed to replicate conventional consumer electronics. The impact of the demonstrations on student interest was measured by creating paired pairs of demos of raw and polished quality. These were utilized in lectures to 119 students, and post-lecture surveys were conducted to gauge student interest and comprehension. Implementing only a single demonstration in both raw and polished forms, preliminary findings reveal that students in both technical and nontechnical majors score higher in objective assessment and report more interest in the topic when employing raw construction techniques (two-tailed p=0.051 and 0.01 respectively). The findings indicate that demonstrations are more valuable in their raw form.